IN VITRO ANTIOXIDANT AND MOLECULAR DOCKING STUDIES FOR ANTI-ALZHEIMER POTENTIAL OF ETHANOLIC EXTRACT OF ALTERNANTHERA SESSILIS AND LANTANA CAMARA - CH. SARVARAIDU; MOHAMMAD ALI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Oxidative stress significantly contributes to the advancement of Alzheimer’s disease (AD), and antioxidants (AOX) derived from plants are increasingly recognized for their neuroprotective properties. This research examines the in vitro AOX properties and anti-Alzheimer potential of ethanolic extracts of Alternanthera sessilis (EEAS) and methanolic extract of Lantana camara (MELC) through phytochemical screening, AOX assays, gas chromatography–mass spectrometry (GC-MS) analysis, molecular docking (MD), and ADME prediction. Methods: Preliminary phytochemical screening identified the existence of flavonoids, phenolics, Alkaloids, sterols, and glycosides. The evaluation of AOX activity was led through 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and metal chelating assays. GC-MS analysis revealed significant bioactive compounds in both extracts. The phytoconstituents were docked to AD-related targets (Aβ and AChE) to evaluate their binding affinities. ADME properties were assessed utilizing SwissADME. Results: Indicate that both EEAS and MELC demonstrated considerable AOX activity, with MELC presenting lower IC50 values in the DPPH (204.3 μg/mL) and ABTS (327.47 μg/mL) assays relative to EEAS. GC-MS profiling identified compounds with established pharmacological significance. MD revealed multiple compounds exhibiting high binding affinity for AD targets. ADME analysis demonstrated adherence to drug-likeness criteria, indicating potential for oral bioavailability. Conclusion: The research indicates that A. sessilis and L. camara exhibit significant AOX and anti-Alzheimer effects. Phytoconstituents may provide a basis for the advancement of neuroprotective agents. Future in vivo validation is necessary to verify their therapeutic potential.